An Analysis of Political Ethics from the Perspective of Muhammad Arkoun - Surianto, Annisa Pratiwi; Junaidi, Junaidi (JUSPI (Jurnal Sejarah Peradaban Islam), 2024)
This study is grounded in the profound need to comprehend the role of Mohammed Arkoun, a postmodern/contemporary scholar, in revitalizing the potential of Islamic thought in the 21st century. The article underscores Arkoun's significance as an Islamic philosopher who successfully integrates the "authenticity of Islam" with a broad understanding of contemporary social sciences, giving rise to the concept of Applied Islamology. With a life background immersed in two traditions, Islam (Algeria) and France (the West), Arkoun endeavors to reconcile various aspects of life from both civilizations.The research methodology employs descriptive, historical, comparative, and synthetic analysis approaches. Data collection involves extensive literature research on Arkoun's works, both his writings and relevant contributions from other authors. Based on a philosophical-critical examination of the data, it is concluded that Arkoun plays a significant role in shaping an inclusive study of Islam for the future. The findings offer profound insights into Arkoun's contribution to connecting and harmonizing Islamic thought with contemporary social sciences.